Sagot :
Answer:
x=-2
Step-by-step explanation:
[tex]a.)[/tex] -5x+4y=10
[tex]b.)[/tex] 2x+9y=-4
Choose one and make it one variable in terms of y.
-5x+4y=10
4y=10+5x
[tex]y=\frac{10+5x}{4}[/tex]
[tex]y= \frac{5}{2} + \frac{5}{4}x[/tex] → equation 1
Substitute equation 1 to [tex]b[/tex]
[tex]2x+9(\frac{5}{2} + \frac{5}{4}x)=-4[/tex]
[tex]2x+ \frac{45}{2}+ \frac{45}{4}x=-4[/tex]
[tex]2x+ \frac{45}{4}x=-4 -\frac{45}{2}[/tex]
[tex]\frac{53}{4}x = -\frac{53}{2}[/tex]
[tex]x=-\frac{53}{2}[/tex][tex]/\frac{53}{4}[/tex]
[tex]x=-\frac{4}{2}\\x=-2[/tex]